TINGKAT KETERBUKAAN, KOMPETISI DALAM ARUS PERDAGANGAN INDONESIA DI ASIA*: SUATU PENDEKATAN EKONOMETRIKA - Joko S. Usman; Mangara Tambunan; Hermanto Siregar; Anny Ratnawati (Fakultas Pertanian, Universitas Riau, 2011)
The information presented in the seminar is obtained from the research in respect of tradeopenness, competitiveness and flows of our export and import of industrial productsbetween Indonesia and its trading partners in Asia. Research has concluded that tradeopenness has positive relationship with our economic growth.. Indonesian trade flows hassignificant opportunity to augment its performance, substantiated by our finding on speedof convergence test in our bilateral trade with the partners, suggesting that they aredesirable partners for an Asian FTA Further we find that our international trade flows aHeckscher-Ohlin model more than increasing return or products differentiation or still aninter-industry trade rather than intra industry trade, substantiated with positive coefficientTCI variable and low Grubel Lloyd index. However please note that some of our industrialproducts have already well positioned with high Grubel Lloyd index. Combining the abovefindings, the Indonesian international trade policy should be addressed toward increasing itsintra industry trade through appropriate investments and industrial restructuring.Key words: gravity model, openness, trade flows, inter-intra industry trade Asian FTA